Small states in world politics : the international political position and diplomatic influence of the world's growing number of small countries - Henrikson, Alan K. (World Bank WashingtonUS, 1999)
Seeks to show how the international political position and diplomatic influences of small states can be used, by small states themselves, to enhance their role in the world, and in so doing, to make contributions to the international system.